(untitled) (Jurnal Geomine, 2022)
Malino-Sinjai Road, Gowa Regency, is an area prone to landslides in the rainy season, where the geological condition is in the form of the Baturape-Cindako Volcano unit, namely volcanic rock of Pliocene. The research location is on Malino-Sinjai Road, Km ± 54 Parangloe District and Km ± 71 Tinggi Moncong District, Gowa Regency; the average slope of the study area is >45°. This research aims to conduct geological engineering observations on the slopes using lithological discontinuous conditions and regions. Conduct slope stability analysis using the Morgenstern-Price method software and provide technical or design recommendations for the observed slope conditions. The research methodology uses primary data from observations of engineering geology and geometry of the slopes, as well as secondary data from previous studies, books, and the results of laboratory tests of rocks’ physical and mechanical properties. The results of the survey obtained technical geological observation data that the slope (A), which is located on Malino-Sinjai Road Km ± 54 Parangloe District in the form of basalt rock, has a high level of weathering characterized by an average joint distance of 9 cm and the condition of the top of the slope area has become residual soil. In contrast, on the slope (B), located on Malino-Sinjai Road, Km ± 71 Kecamatan Tinggi Moncong, in the form of tuff rock, the weathering is still in the mildly weathered category, and the solid condition is not visible. Based on the results of interpretation using the Morgenstern-Price method, the slope safety factor value (A) is FK 1.101, which is considered unstable based on the minimum standard of the slope safety factor of the Ministry of Public Works in 2014, which is > 1.25. On slope (B), the safety factor value is obtained, namely FK 1.371, where the slope is considered stable or safe. As for technical or design recommendations to prevent ground shaking, slope (A) can use retaining walls or retaining walls and slopes (B) use wire mesh or wire nets around the observation slope.